Anomalous connection of superior vena cava to the left atrium masquerading as epilepsy: A case report with review of literature - Singh Sandeep; Geelani Muhammed; Modi Pranav; Niwaria Yogesh; Shahi Sudhir; Banerjee Amit (Annals of Cardiac Anaesthesia, 2008)
An 11-year-old girl who presented with recurrent epileptic fits was eventually found to have a superior vena cava draining into the left atrium. There was no atrial septal defect. The patient underwent a successful surgical correction.